The Pets at Home Guide to Tropical Fish : Expert Advice on Caring for Your Pet - Edited by Anne Mcdowall (England Interpet Publishing Ltd., 2006)
"Expert advice on pet care, tips on being a responsible owner, selecting your new tropical fish". -- cover.
Include Color Illustration
Keywords: Budgerigar -- Rabbits -- Goldfish -- Tropical fish